2009
DOI: 10.1200/jco.2009.27.18_suppl.cra8003
|View full text |Cite
|
Sign up to set email alerts
|

Vandetanib plus docetaxel versus docetaxel as second-line treatment for patients with advanced non-small cell lung cancer (NSCLC): A randomized, double-blind phase III trial (ZODIAC)

Abstract: CRA8003 Background: Vandetanib is a once-daily oral inhibitor of VEGFR, EGFR and RET signaling. Addition of vandetanib to docetaxel (doc) prolonged progression-free survival (PFS) in a randomized phase II study in patients (pts) with previously treated NSCLC (Heymach et al, JCO, 2007). Methods: The primary objective was to determine whether vandetanib 100 mg/day + doc 75 mg/m2 every 21 days (max 6 cycles) prolonged PFS vs placebo + doc. Secondary endpoints included overall survival, objective response rate (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
2

Year Published

2009
2009
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 0 publications
1
46
0
2
Order By: Relevance
“…7 The inhibitors of VEGF in the therapy of central nervous system malignancy normalizes tumor vasculature and decrease tumor interstitial pressure, leading to an improved access of cytoreductive drugs and radiotherapy efficacy, due to an increased oxygen delivery [39]. However, these agents may also restore the low permability characteristics of normal brain microvasculature, counteracting beneficial effects.…”
Section: The Controversial Effect Of Vascular Normalization In the Trmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The inhibitors of VEGF in the therapy of central nervous system malignancy normalizes tumor vasculature and decrease tumor interstitial pressure, leading to an improved access of cytoreductive drugs and radiotherapy efficacy, due to an increased oxygen delivery [39]. However, these agents may also restore the low permability characteristics of normal brain microvasculature, counteracting beneficial effects.…”
Section: The Controversial Effect Of Vascular Normalization In the Trmentioning
confidence: 99%
“…It appears that bevacizumab can be a component of an effective combination therapy approach to colorectal cancer, non-small-cell-lung cancer (NSCLC), and breast cancer [3][4][5]. Encouraging results have also been obtained when chemotherapy has been used in combination with an anti-VEGF receptor-2 (VEGFR-2) monoclonal antibody (cediranib) [6] and an oral tyrosine kinase inhibitor of VEGFRs and epidermal growth factor receptor (EGFR) (vandetanib) [7,8]. The observation that combining chemotherapy with angiogenesis inhibitors causes increased apoptosis in tumors in vivo [9,10] suggest that angiogenesis inhibitors may have an additive effect when administered in combination with chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Data have recently been reported from three double-blind, randomized, phase III studies of vandetanib in patients with advanced, previously-treated non-small cell lung cancer (NSCLC). [8][9][10] In the ZODIAC (ZactimaÔ in cOmbination with Docetaxel In non-small cell lung Cancer) study, vandetanib in combination with docetaxel produced a significant improvement in progression-free survival compared with docetaxel alone (p < 0.001). [9] Results from the ZEAL (ZactimaÔ Efficacy with Alimta Ò in Lung cancer) [8] and ZEST (ZactimaÔ Efficacy when Studied versus Tarceva Ò ) [10] studies demonstrated activity in NSCLC for the combination of vandetanib with pemetrexed, [8] and for monotherapy with vandetanib.…”
Section: Introductionmentioning
confidence: 99%
“…[45][46][47][48][49] Zodiac compared docetaxel with or without the addition of vandetanib at 100 mg daily or 300 mg daily in 1391 patients. A statistically significant increase in PFS was seen with vandetanib at either dose, compared to docetaxel alone (12 weeks versus 18.7 weeks and 17 weeks respectively).…”
Section: Pharmacology and Pharmacokineticsmentioning
confidence: 99%